Contributions of the São-Borjense Mother-Baby Strategy to qualify the maternal and child health care network - Camila Malgarim; Manoella Malgarim; Alexandre Antonio Naujorks; Francisca Georgina Macedo de Sousa; Kerstin Hämel; Dirce Stein Backes (Universidade Federal de Santa Maria, 2020)
Objective: to describe the contributions of the São-Borjense Mother-Baby Strategy to qualify the local maternal and child health care network. Method: this is an action research carried out in the municipality of São Borja, Rio Grande do Sul, between March/2018 and October/2019, after one year of implementation of the Strategy in that location. Data collected through ten focus groups and categorized by Strategic Focal Analysis, with the participation of local managers, health professionals and pregnant women, totaling 55 participants. Results: the data, organized and categorized, resulted in two categories: Contributions that transcend technical and professional practice and Contributions aimed at qualifying the São-Borjense Mother-Baby Strategy. Conclusion: the São-Borjense Mother-Baby Strategy contributed, in an affirmative and prospective way, to qualify the local maternal and child health care network, especially with regard to the relationships and interactions between professionals and pregnant women and (re)organization of flows and intervention processes in the network.